Use of the pentasaccharide fondaparinux as an anticoagulant during haemodialysis - Kalicki, Robert M.; Aregger, Fabienne; Alberio, Lorenzo; Lämmle, Bernhard; Frey, Felix J.; Uehlinger, Dominik E. (Thrombosis and Haemostasis, 2007)
No data about the use of the pentasaccharide fondaparinux, a highly selective indirect inhibitor of factor Xa,in patients treated with haemodialysis are available. Therefore, we investigated the pharmacokinetics and -dynamics of fondaparinux in 12 patients during haemodialysis. The anti-Xa activity (expressed as fondaparinux equivalent) was monitored, a semiquantitative clotting scale (SQCS) ranging from 0 (no visible traces of coagula) to 3 (complete clotting of the dialysis circuit) was applied, and the digital compression time necessary to achieve haemostasis at the puncture site was determined. After an initial period, when the regular heparin dose was replaced once weekly by fondaparinux, 0.05 mg/kg, the pentasaccharide was administered for nine consecutive haemodialysis sessions. Peak anti-Xa activity increased from 0.61 ± 0.14 μg/l after the first dose to 0.89 ± 0.24 μg/l after dose 9 (P<0.001), whereas predialysis anti-Xa activity steadily rose to 0.32 ± 0.09 μg/l (P<0.001). A sufficient but slightly less effective anticoagulation with a mean SQCS of 1.19 ± 0.71 (n=121) was obtained by fondaparinux as compared with 0.65 ± 0.58 (n=60, P<0.005) by 4,825 ± 1,703 U of unfractionated heparin. Mean digital compression time rose slightly during fondaparinux from 23.7 ± 7.4 minutes to 24.8 ± 7.5 minutes (P<0.05) and, more important, six of the 12 patients reported minor bleeding problems during the interdialytic interval. Thus, fondaparinux can be used to prevent circuit clotting during haemodialysis; however, accumulation results in an interdialytic increase of anti-Xa activity. Therefore, fondaparinux should be reserved for patients requiring systemic anticoagulation on the days off dialysis.
Keywords: Dialysis; anticoagulation; pentasaccharide; fondaparinux; anti-Xa